2014
DOI: 10.1128/aac.01324-13
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with Fluoroquinolone or Trimethoprim-Sulfamethoxazole for Treatment of Stenotrophomonas maltophilia Infections

Abstract: The treatment of choice for Stenotrophomonas maltophilia is trimethoprim-sulfamethoxazole (SXT). Fluoroquinolones (FQs) have in vitro activity against S. maltophilia; however, there is limited published information on their effectiveness. The purpose of this study is to compare the effectiveness of FQs and SXT for the treatment of S. maltophilia. A retrospective review of 98 patients with S. maltophilia infections who received SXT or FQ monotherapy was conducted. Patients >18 years old with a positive culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 22 publications
2
99
1
Order By: Relevance
“…Levofloxacin may be an alternative drug to treat SM infection [35]. Recent studies indicated that levofloxacin was not inferior to TMP-SMZ for the treatment of SM infection or bacteraemia [36], [37]. However, rapid resistance to fluoroquinolones has been observed in vitro and in vivo [2].…”
Section: Discussionmentioning
confidence: 99%
“…Levofloxacin may be an alternative drug to treat SM infection [35]. Recent studies indicated that levofloxacin was not inferior to TMP-SMZ for the treatment of SM infection or bacteraemia [36], [37]. However, rapid resistance to fluoroquinolones has been observed in vitro and in vivo [2].…”
Section: Discussionmentioning
confidence: 99%
“…SXT resistance in S. maltophilia is not known to be caused by efflux systems but has been linked to class 1 integrons and ISCR elements (1). This suggests that spontaneous resistance is less likely to emerge with SXT monotherapy, although a clinical trial comparing the two antibiotics is warranted (21,22).…”
mentioning
confidence: 99%
“…Since resistance from a single SNV emerged during a short course of ciprofloxacin, clinicians should be cautioned about using quinolone monotherapy for S. maltophilia bacteremia, as highlighted in recent retrospective studies (21,22). The wide variety of MDR phenotypes and unreliability of DST results have created uncertainty about appropriate treatment for S. maltophilia, but SXT remains the most common choice for monotherapy (1,21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study showed that TMP-SMZ and fluoroquinolones are equally effective once used as monotherapies in treating S. maltophilia -related infections (53). MDR isolates of S. maltophilia have shown excellent responses to combinations of new fluoroquinolones and tetracycline derivatives (46).…”
Section: Antimicrobial Susceptibility and Therapeutic Optionsmentioning
confidence: 99%